Effectiveness of Zr(IV)-Loaded Banana Peels Biomass for the Uptake of Fluoride Anion from Water - Aryal, Ram Lochan; Poudel, Bhoj Raj; Pokhrel, Megh Raj; Paudyal, Hari; Ghimire, Kedar Nath (Journal of Institute of Science and Technology, 2021)
The present study reports the fluoride uptake potential of Zr(IV)-loaded saponified banana peels (Zr(IV)-SBP) from water. Zr(IV)-SBP was synthesized by loading Zr(IV) onto banana peel biomass after saponification and sorbent characterization was performed by using different techniques including FE-SEM (Field Emission Scanning Electron Microscopy), FTIR (Fourier Transform Infra-Red) spectroscopy and zeta potential analysis. Batch experiments were carried out to examine the monitoring factors for the uptake of fluoride onto the investigated adsorbent. The optimal pH and contact time were found to be 2.94 and 300 minutes, respectively. The results from characterization techniques concurred that Zr(IV)-SBP have prominent adsorption sites favorable for the sorption of fluoride ions. The sorption behavior of fluoride onto Zr(IV)-SBP was best fitted with the Langmuir adsorption isotherm and pseudo-second-order kinetics model. The maximum adsorption capacity of Zr(IV)-SBP was 36.02 mg/g using the Langmuir isotherm model. The coexisting ions like chloride and nitrate caused very small interference, elevated concentration of sulphate notably lowers the fluoride adsorption percentage in the binary system, and the sorption using multiple systems was lowered significantly which is due to the synergistic effect of co-existing interfering ion. The adsorbed fluoride was completely desorbed using 2M NaOH solution. Fluoride sorption performance of Zr(IV)-SBP demonstrated that it can be a low cost, environmentally benign and one of the highly potent alternatives for the remediation of fluoride ions to avoid ablation on the water.